Effects of triglycerides levels in human whole blood on the extraction of 19 commonly used drugs using liquid–liquid extraction and gas chromatography–mass spectrometry. (2015) - Huang, ZhiBin; Yu, Tianfang; Guo, Lin; Lin, Zebin; Zhao, ZiQin; Shen, Yiwen; Jiang, Yan; Ye, Yonghong; Rao, Yulan
Abstract: Liquid–liquid extraction (LLE) is the most commonly sample preparation procedure used by forensic toxicologists in China for screening drugs in whole human blood. It extracts numerous substances from blood including targeted drugs and interfering substances, specifically triglycerides (TG). With increasing prevalence of hyperlipidemia, the influences of TG on LLE and on subsequent analysis with gas chromatography–mass spectrometry (GC–MS) may become a major issue for forensic laboratories. This study aims to elucidate the influences of TG on LLE and to provide possible solutions to this problem. Nineteen commonly encountered drugs in forensic cases were spiked to human whole blood with different TG concentrations. Diethyl ether, ethyl acetate/hexane mixed solutions, chlorobutane and several other frequently used solvents were tested for the extraction of drugs from spiked whole blood. The supernatant organic layer was evaporated to dryness and reconstituted with methanol. The resultant products were analyzed by GC–MS, and the extraction recovery was calculated. LLE with diethyl ether, ethyl acetate/hexane (9:1) and chlorobutane all possessed effective and reliable extraction recoveries for blood sample with low TG concentrations (0.63–6.85 mmol/L). At high TG concentrations, diethyl ether produced a highly turbid substance that could not be further analyzed using GC–MS. Extraction recoveries drastically dropped for ethyl acetate/hexane (9:1) mixture at high TG concentrations, while chlorobutane experienced minimal drops in extraction recoveries. In conclusion, TG levels in whole blood noticeably influence drug recovery to variable extents depending on the LLE solvent. Chlorobutane showed minimal influences from TG content in whole blood and thus is the recommended LLE solvent for forensic drug extraction.